Pengaruh Pendidikan Kesehatan Tentang Pemberian Pertolongan Pertama (Management Airway) Korban Tenggelam di Kolam Renang Gunung Merah, Bandar Jaya, Kecamatan Terbanggi Besar, Kabupaten Lampung Tengah - Luthfia Romadhoni; Ari Wahyuni (Majority, 2021)
Airway management is the most important thing in resuscitation and requires special expertise in emergency management, therefore the first thing to do to assess is the smoothness of the airway, which includes examination of the airway that can be caused by foreign objects. Especially during drowning, the airway can become clogged with fluids and water so that the oxygen supply in the body is hampered. Research Objectives The general objective of this study is to improve abilities airway management skills of swimming pool guards, swimming pool cleaners, private swimming teachers, and swimmers in the Gunung Merah Swimming Pool, Bandar Jaya, Terbanggi Besar District, Central Lampung. This research is an experimental study with a Pre-Test-Post Test on 20 respondents through testing the research hypothesis. Statistics: The paired group test used the Wilcoxon nonparametric test. Result: Based on the results of the Wilcoxon analysis test it can be seen. It was concluded that 20 respondents who did training in simulation action by means of airway management training for drowning victims. The conclusion is with the Wilcoxone test that the majority of respondents have good knowledge in terms of emergency handling capabilities, especially in air line management measure the p value 0.001, which means that there is a significant difference between before and after practice. Conclusion: Airway management training for pool workers, pool guards, swimming private teachers, and swimmers is very necessary to improve the ability of action skills.